Safety of animal food imported into the European Union in light of the European Union-Mercosur Partnership Agreement - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2025)
The purpose of the considerations is to determine the result of comparing the EU safety requirements for food of animal origin with the terms of the EU-Mercosur Partnership Agreement regarding the safety of these products. It is also to formulate an answer to the question of whether food of animal origin intended to be imported into the European Union would have to meet the same standards for ensuring safety as food produced and marketed in the EU. The author concludes, among other things, that the European Union retains the authority to verify the safety standard of food of animal origin. The EU-Mercosur agreement could also remove technical barriers to trade between the parties, if an adequate degree of international harmonization of sanitary and phytosanitary standards has been achieved. Compliance instruments, such as due diligence under the EUDR for certain products and conformity assessment for all products covered by the EU-Mercosur agreement, could potentially guarantee common and uniform consumer health protection.